Síntese de cerâmicas ferroelétricas de PLZT–análise composicional e mecanismos de vacâncias - Silva, Atair Carvalho da [UNESP] (2013)
The objective of the present work was related to the synthesis of lanthanum modified lead zirconate titanate ferroelectric ceramics, considering the occurrence of vacancies at the A-site ( or B-site ( of the perovskite structure, through the stoichiometric chemical formulas ( ) and , respectively, where x is the molar fraction of lanthanum with values of 0.02, 0.04, 0.06, 0.08, 0.10 and 0.12, and y = 0.70 (representing the Zr/Ti=70/30 ratio). The method used for the synthesis of the samples was the Solid State Reaction (SSR), well known as the conventional oxide mixture or ceramic method. The calcination process was performed at 900° C for 2h. Pellets-shaped ceramics samples were obtained from uniaxial and isostatic pressing, followed by the sintering process at a temperature of 1250°C, during 2h, under lead atmosphere containing, being that for some compositions low concentration of PbO was observed. For determining the temperature of thermal events was used technique called Differential Thermal Analysis (DTA). The formation of the desired ferroelectric phases was confirmed by X-ray Diffraction (XRD), room at temperature, performed on the calcined powder and the sintered ceramic samples. The Scanning Electron Microscopy (SEM) technique was used to investigate the microstructure of the ceramics, revealing an average grains size on m scale. The EDS microanalysis confirmed the desired composition. The dielectric properties were investigated in a wide frequency range and temperature in order to obtain the Curie temperature (TC) and verify the dielectric character of the studied system. The obtained results have been discussed and compared according to the theories described in the current literature